Colonization of everyday life on Instagram through Filipino influencers - Rosales, Teresa Joanna Castro 1998-
"This study examines how everyday life is being colonized in and by social media, specifically through Instagram. In order to do this, this study looks at two things - the accounts of three Filipino Instagram-famous personalities and the medium that is Instagram. I used Guy Debord's theory on the society of the spectacle (1967), Henri Lefebvre's critique of the everyday life (1958), and Raoul Vaneigem's theory on the colonization of everyday life (1967) as guides for my theoretical framework and a thematic analysis for my methodology. Using Discursive Narrative Visual Analysis to analyze the posts of the three Filipino influencers, I found that there are two degrees of colonization of everyday life on Instagram. Posts that influencers label because of partnerships are colonized by brands. Posts that influencers label for publicity are colonized by the ideology of Capitalism."